Stroški dela v različicah delovnih pogojev in izkoriščenosti strojev za sečnjo - Krč, Janez (Zbornik gozdarstva in lesarstva, 2004)
In contemporary wood production technologies, there is an urgent demand for precise forest operation cost analyses. Some examples of cost calculation for mechanized cutting are analyzed. A new computer procedure for cost calculationis presented. The procedure enables forest operation cost calculation and analyses of productivity in different work conditions. Forest operation productivity for small and big harvesters in coniferous and deciduous stands can be selected. The program also enables analyses of influential factors which affect mechanized cutting costs. The most important influential factor is the operational degree of utilization, which is influenced by transfer of machines between work fields, size of work fields, cutting and tree volume. It is also possible to conduct sensitivity analyses of machine utilization expressed in working hours per year. Generally, sensitivity analyses showed that the labour cost differences are highest at the cutting volume of 40-50m3/ha and 0.3 m3 mean tree volume.
Keywords: strojna sečnja; stroški dela